Strategies to induce natural killer cell tolerance in xenotransplantation - Lopez, Kevin J.; Cross-Najafi, Arthur A.; Farag, Kristine; Obando, Benjamin; Thadasina, Deepthi; Isidan, Abdulkadir; Park, Yujin; Zhang, Wenjun; Ekser, Burcin; Li, Ping (Frontiers in Immunology, 2022)
Eliminating major xenoantigens in pig cells has drastically reduced human antibody-mediated hyperacute xenograft rejection (HXR). Despite these advancements, acute xenograft rejection (AXR) remains one of the major obstacles to clinical xenotransplantation, mediated by innate immune cells, including macrophages, neutrophils, and natural killer (NK) cells. NK cells play an ‘effector’ role by releasing cytotoxicity granules against xenogeneic cells and an ‘affecter’ role on other immune cells through cytokine secretion. We highlight the key receptor-ligand interactions that determine the NK cell response to target cells, focusing on the regulation of NK cell activating receptor (NKG2D, DNAM1) and inhibitory receptor (KIR2DL1-4, NKG2A, and LIR-1) signaling pathways. Inhibition of NK cell activity may protect xenografts from cytotoxicity. Recent successful approaches to reducing NK cell-mediated HXR and AXR are reviewed, including genetic modifications of porcine xenografts aimed at improving pig-to-human compatibility. Future directions to promote xenograft acceptance are discussed, including NK cell tolerance in pregnancy and NK cell evasion in viral infection.